Kesadaran Hukum Pelaku Pernikahan Dini dalam Pencatatan Pernikahan di Kandangserang - Hidayat, Mufti (Al-Hukkam: Journal of Islamic Family Law, 2022)
Early marriage still occurs in various regions in Indonesia, therefore, the authors are interested in researching the factors of early marriage, how the practice of early marriage takes place, the importance of discussing the legal awareness of marriage registration so that early marriage does not occur, as happened in Wangkelang Village, Kandangserang Subdistrict, Pekalongan Regency, the practice of registering marriages is still low by the Wangkelang Village Community. The results obtained show that many Wangkelang Village people have early marriages, their marriages are not registered, the marriage is not registered because of the early marriage factor, it has been from the past that the people of Wangkelang Village practice early marriage, early marriage is carried out by not being registered with the KUA, the legal awareness of the people of Wangkelang Village regarding marriage registration is lacking, along with the reasons and objectives for doing early marriage are: first, keeping the name both family, secondly, eliminating parental worries, those two goals are what make ordinary people practice early marriage, early marriage occurs because of factors: economy, education and association/habits, these habitual factors make the practice of early marriage continue to occur, on awareness the law of perpetrators of early marriage in the registration of marriages in Kandangserang, which is contrary to the applicable legal rules, where the marriage must be registered, such as in the Regulation of the Minister of Religion of the Republic of Indonesia, and the problem is in early marriage in Kandangserang.